Du « petit Lavisse » au « petit Labouysse » ? Quels outils pour former à l’histoire de l’espace occitan ? - Yan Lespoux (Lengas)
How can Occitan teachers train themselves to teach the history of the Occitan-speaking area? There are no specifically dedicated school manuals, and works of popularization are scarce. Besides, when they exist, these works often tend to approach Occitan history from an angle which is closely connected with a form of counter-history designed to balance French history as it is taught at school – to balance, at the very least, the type of French history that commonly surfaces in the collective mind in the form of the “national narrative”.